Do citizens of the former Soviet Union trust state institutions and why: The case of Azerbaijan. Issue 3 (September 2017) - Valiyev, Anar; Babayev, Azer; Huseynova, Hajar; Jafarova, Khalida
Abstract: This study examines the trust in political institutions in Azerbaijan using the data from the survey Caucasus Barometer (CB) conducted by the Caucasus Research Resource Center (CRRC) in 2012–2013. Two hypotheses – cultural and institutional – were tested. The study partially confirms the previous findings that national culture, as well as individual socialization (macro and micro-cultural theories) are the main determinants of trust in Azerbaijan. Meanwhile, government performance and individual evaluation (macro-and micro institutional theories) did not affect much on the trust level in the country.